Framing war in the age of algorithmic mediation: A comparative multimodal analysis of AFP, reuters, and AP’s coverage of the Russo–Ukrainian war - Li, Dongyong; Lin, Quanming; Nor, Nur Haniz Mohd; Tan, Kim Hua (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates how three major international news agencies, Agence France-Presse (AFP), Reuters, and the Associated Press (AP), construct narrative frames in their coverage of the Russo–Ukrainian War. Employing a mixed-methods approach that integrates content analysis, critical discourse analysis, and visual examination, the study analyzes 1,200 articles from each agency published between February 2022 and August 2023, focusing on four framing dimensions: war legitimacy, actor representation, economic discourse, and national image. The analysis reveals distinct framing strategies across these agencies, particularly regarding the legitimacy and attribution of responsibility in the war. While AFP situates the war within broader geopolitical contexts by emphasizing historical continuity and systemic factors, Reuters adopts a moralistic binary narrative characterized by emotionally charged language and personalized portrayals of actors. In contrast, AP employs a hybrid approach, combining neutral reporting structures with subtle evaluative elements. These textual differences extend into economic framing, reflecting each agency’s institutional priorities. Reuters emphasizes the global economic repercussions of the war, AFP prioritizes European security concerns, and AP integrates normative assessments into discussions of economic sanctions. Furthermore, visual framing strategies, such as symbolic imagery, color schemes, and camera angles, reinforce these textual differences, shaping audience perceptions emotionally and ideologically. Overall, this study contributes to media and war scholarship by proposing a comprehensive, multidimensional framing model and enhancing methodological rigor through multimodal analysis, ultimately informing media literacy and editorial practices during international crises.